The Fashion of Federalism in Nepal: Challenges and Opportunities (PAAN Journal, 2024)
This article examines federalism as a political system combining self-rule and shared rule, clarifying the latter's meaning beyond mere participation in central government decisions. The focus is on Nepal's transition from a historically unitary system to a federal structure, a response to longstanding desires for regional development and the elimination of inequalities. This article is based on the review of existing literature. It is also based on secondary data and information and findings of previous research work especially in a thematic approach. The study traces the evolution of Nepal's federal system from its inception, influenced by societal mobilizations and a changing political landscape. The importance of federalism lies in empowering diverse communities while fostering collaboration at different government levels. The article also reviews global perspectives on federalism, emphasizing its role in ensuring peace, democratic resilience, service delivery, and efficient decision-making in diverse, large countries. Key findings highlight the need for active engagement and cooperation between the federal and subnational governments for a successful federalism in Nepal. Nepal's hourglass-shaped federal model effectively distributes power but grapples with fiscal centralization and revenue disparities, underscoring the need for continuous implementation and intergovernmental collaboration for efficient public service delivery. The study emphasizes the significance of honest and dedicated implementation by political parties and advocates for a federal system that guarantees the rights and autonomy of minority groups. Ultimately, Nepal's journey towards federalism strives to correct historical disparities and create an inclusive democracy, fostering economic development at the state level and positioning federal states as economic centers. The federal government's critical role lies in ensuring the security, prosperity, and rights of the people, unlocking the potential of federalism for Nepal's future.